From the Reindeer Path to the Highway and Back – Understanding the Movements of Khanty Reindeer Herders in Western Siberia - Stephan Dudeck (Journal of Ethnology and Folkloristics)
The following article explores the meaning of roads and the practices of movement for a small group of forest inhabitants in the Western Siberian lowlands on the middle Ob. The indigenous people known as the Khanty live as reindeer herders, fishermen and hunters in the midst of oil fields in the Surgut Rayon. The article examines their emic point of view opposed to the evaluation of the state administration.